Pengaruh Model Pembelajaran Think Pair Share Terhadap Hasil Belajar Fisika Siswa - Sulindra, I Gusti Made; Hermansyah, Hermansyah; Sentaya, I Made; Yahya, Fahmi (Indonesian Publication Center, 2020)
A good learning process is one that can help students construct their knowledge, skills, and attitudes to solve every problem in their daily lives. To achieve such a learning process, the Think Pair Share learning model is needed as an alternative solution. The purpose of this study was to determine the effect of the Think Pair Share learning model on high school students' physics learning outcomes. This study was a quasi-experimental study with a pre-test post-test control group design. The research population consisted of all students at one of the senior high schools in Sumbawa, while the research sample was divided into two groups of 11th-grade science students: the experimental group and the control group. The research instrument used was a test. The data were analyzed using a t-test at a significance level of 0.05. The results showed that the physics learning outcomes of students in the experimental group were higher than those in the control group, and the calculated t-value was > t-table, namely 6.430 > 1.684. Therefore, it can be concluded that the TPS learning model has an effect on the physics learning outcomes of high school students.